Role of 18F-Fluoro-D-deoxyglucose PET/CT in Diagnosing Surgical Site Infection After Spine Surgery With Instrumentation. Issue 2 (15th January 2015) - Inanami, Hirohiko; Oshima, Yasushi; Iwahori, Tomoyuki; Takano, Yuichi; Koga, Hisashi; Iwai, Hiroki
<x xml:space="preserve">Abstract</x> Study Design. Retrospective case series. Objective. To investigate the effectiveness of positron emission tomography/computed tomography (PET/CT) in diagnosing surgical site infection (SSI) after spinal surgery with instrumentation. Summary of Background Data. Several reports have indicated the usefulness of 18F-fluoro-D-deoxyglucose (F-18 FDG) PET in detecting sites of infection including spinal infection sites. However, no report has documented the efficacy of PET/CT in detecting SSI after spinal surgery with instrumentation. Methods. A total of 811 consecutive case patients who underwent minimally invasive posterior lumbar interbody fusion surgery with instrumentation from December 2008 to February 2012 were enrolled. Of these, for all case patients clinically suspected as having SSI by laboratory data and clinical symptoms, PET/CT was performed. Six patients with no apparent sign of SSI served as a control group. Image data were evaluated by 2 nuclear medicine physicians blinded to the clinical and pathological results. The data were quantitatively analyzed by the maximum standardized uptake value as an index of F-18 FDG uptake. Results. Visual assessment by PET/CT revealed that all 8 patients with suspected SSI were positive for infection whereas all 6 controls without apparent infection were negative for infection. There was a statistically significant difference in the maximum standardized uptake values (mean and range) between the SSI and control groups (9.0 and 5.5–14.7 vs. 3.3 and 2.0–4.3, respectively; P = 0.003). All 8 patients underwent surgical debridement with selective implant removal and achieved a good clinical course. Conclusion. PET/CT was effective in diagnosing SSI and identifying infection sites despite the presence of spinal instruments. Although further studies with a larger number of patients are required, PET/CT presents a good candidate for detecting early-phase SSI after instrumented spinal surgery. Level of Evidence: 4